Copper electrodeposition for nanofabrication of electronics devices - Akolkar, Rohan N.; Barkey, Dale P.; Yokoi, Masayuki; Kondo, Kazuo (Nanostructure Science and Technology,, 2014)
This book discusses the scientific mechanism of copper electrodeposition and it's wide range of applications. The book will cover everything from the basic fundamentals to practical applications. In addition, the book will also cover important topics such as: • ULSI wiring material based upon copper nanowiring • Printed circuit boards • Stacked semiconductors • Through Silicon Via • Smooth copper foil for Lithium-Ion battery electrodes This book is ideal for nanotechnologists, industry professionals, and practitioners.